2014
DOI: 10.1186/1472-6882-14-318
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound-assisted extraction of flavonoid compounds and their pharmaceutical activity from curry leaf (Murraya koenigii L.) using response surface methodology

Abstract: BackgroundExtraction prior to component analysis is the primary step in the recovery and isolation of bioactive phytochemicals from plant materials.MethodsResponse surface methodology was applied to optimize ultrasound-assisted extraction conditions followed by ultra high performance liquid chromatography (UHPLC) to achieve high catechin, myricetin, and quercetin contents, and high antioxidant and anticancer activities in the curry leaf extracts. The antioxidant and anticancer activities of the leaf extracts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 26 publications
5
28
0
Order By: Relevance
“…Similar results have been obtained for UAE of phenolic compounds from Cassia auriculata [41], curry [42], and fresh tulsi leaves [43].…”
Section: Effects Of Ultrasound Power and Frequency On The Total Contesupporting
confidence: 86%
“…Similar results have been obtained for UAE of phenolic compounds from Cassia auriculata [41], curry [42], and fresh tulsi leaves [43].…”
Section: Effects Of Ultrasound Power and Frequency On The Total Contesupporting
confidence: 86%
“…Of these, solvent, supercritical fluid, microwave-assisted and ultrasonic-assisted extraction are notable. Microwave-assisted extraction and ultrasound-assisted methods are used to detect antioxidant and anticancer bioactive components in the plant extracts [35,36]. Imsanguan et al described conventional solvent extraction, with different modifications at different temperatures (32-60°C), using 100 ml hexane at a rotating speed of 200 rpm for 24 h to extract γ-oryzanol from rice bran [37].…”
Section: Extraction Isolation and Identification Of The Active Compomentioning
confidence: 99%
“…Ghasemzadeh et al [20] found that ANOVA for predicted model of antioxidant activity was significant (F-value 17.21, P < 0.0001) with a good coefficient of determination (R 2 = 0.98). They also observed that extraction variables showed significant (P < 0.01) quadratic and linear effects on the antioxidant activity and the predicted model obtained for DPPH (Y 4 ) was as follows:…”
Section: Phenolic and Antioxidant Compound Extraction From Plant Matementioning
confidence: 99%
“…To optimize the ultrasound-assisted extraction conditions followed by ultrahigh performance liquid chromatography (UHPLC) to achieve high catechin, myricetin, and quercetin contents, and high antioxidant and anticancer activities in the curry leaf extracts, RSM was applied by Ghasemzadeh et al [20]. They used the central composite experimental design (3-level, 3-factorial) to determine the optimum extraction parameters affecting the extraction yields of catechin (Y1), myricetin (Y2), quercetin (Y3), and antioxidant activity (Y4) of curry leaf extracts [20].…”
Section: Statistical Approaches With Emphasis On Design Of Experimentmentioning
confidence: 99%
See 1 more Smart Citation